a)
$⇔ x^2 + 4x + 4 - x^2 + 25 = 4$
$⇔ 4x + 29 = 4$
$⇔ 4x = - 25$
$⇔ x = \dfrac{-25}{4}$
b)
$⇔ x^2 - 4x - x^2 + 14x + 49 = 3$
$⇔ 10x = -46$
$⇔ x = \dfrac{-46}{10}$
c)
$⇔ x^2 - 16 - (x^2 - 5x + 3x - 15) = 7$
$⇔ x^2 - 16 - x^2 + 2x + 15 = 7$
$⇔ 2x = 8$
$⇔ x = 4$
a) (x + 2)² - (x - 5)(x + 5) = 4
x² + 4x + 4 - x² + 25 = 4
4x + 29 = 4
4x = 4 - 29
4x = -25
x = -25/4
b) x(x - 4) - (x - 7)² = 3
x² - 4x - x² + 14x - 49 = 3
10x - 49 = 3
10x = 3 + 49
10x = 52
x = 52/10
c) (x - 6)(x + 6) - (x + 3)(x - 5) = 7
x² - 36 - x² + 5x - 3x + 15 = 7
2x - 21 = 7
2x = 7 + 21
2x = 28
x = 28/2
x = 14